2020
DOI: 10.1038/s41598-020-63322-y
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II genotyping of admixed Brazilian patients with type 1 diabetes according to self-reported color/race in a nationwide study

Abstract: The HLA region is responsible for almost 50% of the genetic risk of type 1 diabetes (T1D). However, haplotypes and their effects on risk or protection vary among different ethnic groups, mainly in an admixed population. We aimed to evaluate the HLA class II genetic profile of Brazilian individuals with T1D and its relationship with self-reported color/race. This was a nationwide multicenter study conducted in 10 Brazilian cities. We included 1,019 T1D individuals and 5,116 controls matched for the region of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 30 publications
6
24
0
Order By: Relevance
“…As expected, our results showed that when comparing our T1D group, the CRsr and regional REDOME controls, the DRB1 * 03 and DRB1 * 04 alleles showed an odds ratio of risk for association with T1D, with DRB1 * 04 (30.26%), DRB1 * 03 (29.93%) and the DR3 / DR4 heterozygous genotype (26.32%) as the most frequents. In a large analysis of the T1D population in all Brazilian regions, a result similar to ours was found 46 . It is reported that approximately 30% of individuals with T1D have DR3/DR4 in heterozygosity 6,47 , corroborating our ndings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As expected, our results showed that when comparing our T1D group, the CRsr and regional REDOME controls, the DRB1 * 03 and DRB1 * 04 alleles showed an odds ratio of risk for association with T1D, with DRB1 * 04 (30.26%), DRB1 * 03 (29.93%) and the DR3 / DR4 heterozygous genotype (26.32%) as the most frequents. In a large analysis of the T1D population in all Brazilian regions, a result similar to ours was found 46 . It is reported that approximately 30% of individuals with T1D have DR3/DR4 in heterozygosity 6,47 , corroborating our ndings.…”
Section: Discussionsupporting
confidence: 88%
“…We still found that the most frequent DQA1 alleles were 05:01 (29.14%), and 03:01 (26.82%), and the most frequent DQB1 alleles were 03:02 (32.57%), 02:01 (26.32%), compatible with the fact that these are the most frequent DQA1 and DQB1 alleles associated with T1D 4 . In a study performed by Santos et al, it was observed that in Brazilian individuals with T1D, the same haplotype, DRB1*03:01~DQA1*05:01~DQB1*02:01 (DR3-DQ2), was the most frequently found in this subpopulation of individuals 46 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…T1D is an autoimmune disease and there are several biomarkers serving as risk indicators. A genetic predisposition is required and certain high-risk human leukocyte antigen (HLA) genotypes have been identified [ 1 , 2 , 3 ]. There is a genetic inheritance, but only 15% of patients with T1D have a first-degree relative with the disease.…”
Section: Introductionmentioning
confidence: 99%
“…In admixed populations, individuals who self-identify to the same group frequently have extremely variable genetic ancestries. This is expected, since self-identification involves a complex interplay of social and genealogical components (19) and varies among geographic regions in Brazil (20,21).…”
Section: Introductionmentioning
confidence: 99%